2012
DOI: 10.1021/ic301577a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Reactivity of Dinitrogen Molybdenum Complexes with Bis(diphenylphosphino)amine Derivative Ligands that Form a Unique 4-Membered P–N–P Chelate Ring

Abstract: Five dinitrogen-molybdenum complexes bearing bis(diphenylphosphino)amine derivative ligands (L(R)) that form a unique 4-membered P-N-P chelate ring, trans-[Mo(N(2))(2)(L(R))(2)] (2(R): R = Ph, Xy, p-MeOPh, 3,5-iPr(2)Ph, iPr), were prepared for the purpose of binding a dinitrogen molecule. The corresponding two dichloride-molybdenum complexes, trans-[MoCl(2)(L(R))(2)] (1(R): R = Ph, Xy), were also prepared as comparisons. FT-IR spectra of 2(R) were measured and compared the ν(N≡N) values. Moreover, X-ray crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 131 publications
(87 reference statements)
1
23
0
Order By: Relevance
“…However, unfortunately, we have not yet found any evidence to support our proposal shown in Scheme 22. Recently, Masuda and co-workers have reported the preparation and characterization of several molybdenum− dinitrogen complexes bearing bis(diphenylphosphino)amines as ligands (41) and investigated their catalytic activity toward the formation of N(SiMe 3 ) 3 under ambient reaction conditions (Scheme 21). 43 Here, only a low catalytic activity (4 equiv based on the catalyst) has been found in the use of some molybdenum−dinitrogen complexes as a catalyst. More recently, Meźailles and co-workers have reported the reduction of molecular dinitrogen into N(SiMe 3 ) 3 by using molybdenum complexes bearing a bulky tetradentate phosphine as a ligand (42) under ambient reaction conditions (Scheme 21).…”
Section: Catalytic Formation Of Silylamine Frommentioning
confidence: 96%
See 1 more Smart Citation
“…However, unfortunately, we have not yet found any evidence to support our proposal shown in Scheme 22. Recently, Masuda and co-workers have reported the preparation and characterization of several molybdenum− dinitrogen complexes bearing bis(diphenylphosphino)amines as ligands (41) and investigated their catalytic activity toward the formation of N(SiMe 3 ) 3 under ambient reaction conditions (Scheme 21). 43 Here, only a low catalytic activity (4 equiv based on the catalyst) has been found in the use of some molybdenum−dinitrogen complexes as a catalyst. More recently, Meźailles and co-workers have reported the reduction of molecular dinitrogen into N(SiMe 3 ) 3 by using molybdenum complexes bearing a bulky tetradentate phosphine as a ligand (42) under ambient reaction conditions (Scheme 21).…”
Section: Catalytic Formation Of Silylamine Frommentioning
confidence: 96%
“…Iron System. As another approach, we have found that Fe(CO) 5 (43) promoted the catalytic conversion of molecular dinitrogen into N(SiMe 3 ) 3 . Thus, with the reaction of Na and Me 3 SiCl with atmospheric molecular dinitrogen in the presence of 43 in THF at room temperature for 20 h, 25 equiv of N(SiMe 3 ) 3 were formed based on the catalyst (Scheme 23).…”
Section: Catalytic Formation Of Silylamine Frommentioning
confidence: 99%
“…Quite recently, other MoÀN 2 or FeÀN 2 complexes were found to promote the transformation of N 2 into 1. [7,[12][13][14] Almost all of the aforementioned catalytic systemsf or the formation of NH 3 and 1 depend on the use of either Mo or Fe complexes as catalysts. Furthermore, Shilov and co-workers previously reported the catalytic reduction of N 2 into NH 2 NH 2 by using ap olynuclearM oc omplex as ac atalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Masuda and coworkers have also prepared several molybdenum‐dinitrogen complexes bearing bis(diphenylphosphino)amine derivative ligands, and have investigated their catalytic activity towards the formation of silylamine under ambient conditions, where 4 equiv. of N(SiMe 3 ) 3 were produced, based on the Mo atom, when trans ‐[Mo(N 2 ) 2 ( L Ph ) 2 ] ( L Ph = N , N ‐bis(diphenylphosphino)aniline) was used as a catalyst (Scheme ) 117…”
Section: Catalytic Formation Of Silylaminementioning
confidence: 99%